The Effectiveness of Using Digital-Based Teaching Materials on Craftsmanship and Entrepreneurship Learning Outcomes of Class XI Muhammadiyah High School Students - Mustika, Mustika; M, Usman; Takdir, Muhammad; Hermansyah, Sam; Kahar, Abdul (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2023)
This study uses a quantitative method with the type of experimental research that aims to determine the effectiveness of using Flip Books on the results of Craft and Entrepreneurship learning for class XI SMA Muhammadiyah Pangsid, Sidenreng Rappang Regency.The population of this study were all 27 students of class XI SMA Muhammadiyah Pangsid, and the sample of this study was 27 people using the total sampling technique, namely by taking the overall sample. The data collection techniques used were documentation techniques, test techniques, and questionnaire techniques. The indicators of effectiveness in this study are based on Sinambela's theory (2006), the three indicators of effectiveness are: learning completeness, timeliness, and student responses. Learning outcomes are a measure of one's success. The results of this study indicate that the average posttest score is 88.0% higher, while the pretest result is 70.9%. The results showed that the use of Flip Books on the learning outcomes of crafts and entrepreneurship in class XI SMA Muhammadiyah Pangsid was declared effective.